Pengaruh Latihan Plyometric Box Jump Terhadap Hasil Lompat Jauh Gaya Jongkok Pada Siswa Kelas V SDN 19 Kota Bengkulu - Asep Krisna Wijaya Utama; Muhammad Sidik Juarsa (Educative Sportive, 2026)
This study is entitled The Effect of Plyometric Box Jump Training on Squat Style Long Jump Results in Fifth Grade Students of SDN 19 Bengkulu City. The squat style long jump is a branch of athletics that requires strength, speed, and good body coordination. However, in the field it was found that students' abilities in performing long jumps are still not optimal, one of which is caused by the lack of proper training and limited supporting facilities. This study aims to determine the effect of plyometric box jump training on improving squat style long jump results. This type of research is an experiment with a one-group pretest-posttest design, which involves initial measurements (pretest), treatment in the form of plyometric box jump training, and final measurements (posttest). The study was conducted in the field of SDN 19 Bengkulu City with a sampling technique using total sampling, so that all fifth grade students were used as research samples. The research instruments were long jump tests and measurements, with data collection techniques using performance tests assessed through a standardized assessment rubric. Data analysis was carried out using a one-sample t-test to compare the average results of the pretest and posttest. The analysis results show that the calculated t value is greater than the t table, which means there is a significant effect of plyometric training on improving the results of the squat style long jump. The conclusion of this study is that plyometric box jump training can significantly improve students' squat style long jump abilities. This training is recommended to be implemented in sports training programs in elementary schools, especially in developing basic athletic skills such as the long jump. This study also provides an important contribution to the world of sports training, especially in optimizing student performance in jumping sports.